Pengukuran Kinerja Keuangan Pemerintah Desa Menggunakan Analisis Value for Money di Desa Pasirnangka - Sri Pujiyanti; Susilowati Susilowati; Erni Yulianti (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to measure the financial performance of the Pasirnangka Village Government for the 2020–2024 period using the Value for Money (VfM) approach, which includes three main indicators: economy, efficiency, and effectiveness. The study uses secondary data obtained from the Village Budget Realization Report (LRA) of Pasirnangka Village and is analyzed descriptively using ratio calculations in accordance with Minister of Home Affairs Regulation No. 600.900.327 of 1996. The results indicate that, in general, the financial performance of Pasirnangka Village is effective and efficient. However, the economic aspect faced challenges in 2022 and 2024. The inefficiency in 2022 was due to a new policy under the Regent Regulation of Tangerang No. 37 of 2022, which required the budgeting of the Decent Housing Program (RTLH) that was not anticipated in the initial APBDes. In 2024, rising inflation caused prices of goods and services to exceed budgeted amounts. Nevertheless, efficiency and effectiveness remained maintained, with revenue generally meeting or exceeding targets. These findings highlight the importance of accurate and adaptive budget planning in response to changing conditions and new policies. The study recommends several strategic steps to improve village financial performance, including enhancing budget planning accuracy, anticipating new policies, and adjusting projections for goods and services prices. Implementing these recommendations can ensure the sustainability of Pasirnangka Village’s financial performance, support effective, efficient, and economical use of the budget, and maintain optimal public service delivery. This study contributes valuable insights for village financial management and serves as a reference for other villages to systematically apply Value for Money analysis to increase transparency and accountability.